Technical Study of Blasting Geometry and Powder Factor of Fragmentation at Pit 3 Banko Barat PT Bukit Asam Tbk - Hermita Ramadhini; Irvani Irvani; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
Mining PT Bukit Asam Tbk is one of the company that works in coal mining. One of the demolition activities in PT Bukit Asam Tbk is overburden stripping using drilling method and blasting. The success rate of blasting activity can be seen from the fragmentation as the blasting result, where the material size is equally spread is better than boulder. On Pit 3 Banko Barat, blasting using stemdeck results with uneven fragmentation size in condition of same powder factor and burden. This is caused by different rain intensity. Rainfall is causing blasting hole to be wet and decreasing the blasting capabilities of explosives. Blasting using stemdeck results in fragmentation average of 27.19 cm. Blasting without stemdeck based on same burden 8 m, results in fragmentation average of 46.46 cm and fragmentation size chart is obtained that shows increasing value as the powder factor from blasting geometry. That thing is contradictory with theory that the greater powder factor will result in uneven fragmentation size because it is connected with explosives usage. This condition is caused by the same doing to different rock structure on mining location in making blasting geometry design. Blasting without stemdeck based on same powder factor 0.16 kg/m3, results in fragmentation average of 66.26 cm and fragmentation size chart is obtained that is increasing as the value of burden. Smallest fragmentation value in average of 25.12 cm with 8 m burden and 0.17 kg/m3 powder factor. So if smaller fragmentation is needed in the future, then it is recommended to use smaller burden in making blasting geometry design.